Scrambler therapy for the treatment of neuropathic pain related to leukemia in a pediatric patient: A case report. Issue 45 (November 2017) - Park, Hahck Soo; Kim, Won-Joong; Kim, Hyung Gon; Yoo, Seung Hee
Abstract: Rationale: Cancer-related neuropathic pain often responds poorly to standard pain treatments. Scrambler therapy has relieved refractory chronic pain in several uncontrolled clinical trials. Patient concerns: An 11-year-old female patient was suffering from left groin and medial thigh pain after irradiation to the knee. The girl was diagnosed with precursor B-cell lymphoblastic leukemia 2 years ago. Extramedullary relapse of leukemia developed 1 month ago and pain had started. She was treated with oral medications, but she was continuously complaining of severe pain. Diagnosis: Neuropathic pain caused by obturator nerve involvement in leukemia. Intervention: Scrambler therapy. Outcome: Pain reduction. Lessons: Scrambler therapy is noninvasive, is not associated with any complications, causes minimal discomfort during treatment, and is very effective in a pediatric patient with cancer-related neuropathic pain.